Modelling the Adsorption of -Nitrophenol by the Boyd Method in Conjunction with the Finite Element Method - Francisco Zamora; Eduardo Sabio; Silvia Román; Carmen María González-García; Beatriz Ledesma (Adsorption Science & Technology)
Adsorption kinetics are often studied by non-dimensional models that allow a good fitting of the experimental data. Nevertheless, their physical interpretation is very limited because the particle geometry is not considered. In this work, the adsorption kinetics of p -nitrophenol onto two commercial activated carbons with different textural and geometrical characteristics was studied. For this purpose, two types of models were used: zero-dimensional models which do not take the system geometry into account; and the Boyd model, which takes the shape of the adsorbent molecule into account. In contrast to previous published works, the Boyd model was solved by means of the finite element method using the commercial software COMSOL. This paper provides a new insight into the modelling of adsorption kinetics when non-spherical adsorbents are employed.